Surface Electronic Structure Reconfiguration of Hematite Nanorods for Efficient Photoanodic Water Oxidation. Issue 1 (2nd October 2019) - Fu, Yanming; Lu, Ying-Rui; Ren, Feng; Xing, Zhuo; Chen, Jie; Guo, Penghui; Pong, Way-Faung; Dong, Chung-Li; Zhao, Liang; Shen, Shaohua
Abstract : Hematite (α‐Fe2 O3 ) is a promising candidate as a semiconducting photoanode for photoelectrochemical (PEC) water splitting. However, its PEC performance is much limited by the sluggish charge transfer kinetics at the α‐Fe2 O3 /electrolyte interface. Herein, an insulative metal oxide, hafnium dioxide (HfO2 ), is deposited on the surface of α‐Fe2 O3 to engineer the photoelectrode/electrolyte interfacial electronic structure. With the conformal HfO2 overlayer coating, the surface defects of α‐Fe2 O3 are effectively passivated, whereas the charge migration from α‐Fe2 O3 to the electrolyte is blocked by the continuous HfO2 overlayer, leading to a moderate PEC enhancement. In contrast, with HfO2 nanoparticles deposited, the photogenerated holes are not only effectively extracted from the bulk of α‐Fe2 O3 but are also promptly injected into the electrolyte for water oxidation, due to the reconfigurated surface electronic structure. Consequently, the HfO2 nanoparticles‐decorated α‐Fe2 O3 photoanode achieves an onset potential cathodic shift by 180 mV and a 460% photocurrent density enhancement, reaching up to 1.20 mA cm −2 at 1.23 V versus reversible hydrogen electrode as compared with pristine α‐Fe2 O3 . An alternative approach to engineer the photoelectrode/electrolyte interfacial electronic structure to improve the PEC performance for water splitting is demonstrated herein. Abstract : The reconfigurated surface electronic structure in the hafnium dioxide (HfO2 ) nanoparticles‐decorated hematite (α‐Fe2 O3 ) nanorods photoanode not only effectively extracts photogenerated holes from the bulk to surface but also promptly injects photoholes into electrolyte, yielding a remarkably boosted photoelectrochemical water‐oxidation performance improvement as compared with pristine α‐Fe2 O3 and HfO2 conformal overlayer‐passivated α‐Fe2 O3 nanorod photoanodes.